ECOBRICK GOES TO SCHOOL: PELATIHAN MENGOLAH SAMPAH PLASTIK BERBASIS SEKOLAH ADIWIYATA DI SMP NEGERI 25 MALANG - Ni Luh Sinta Yani; Muhammad Sya’roni Zakaria; Nita Sulistia; Rara Vellanieka Aprillaili; Rima Trisna Anggraini; Rizkyta Amalinda; Selamat Budi Hartono; Tika Noviandari; Zaki Nur Anas (Jurnal Abdimas Bina Bangsa, 2024)
Ecobrick goes to school is a training program aimed at teaching students at SMP Negeri 25 Malang how to process plastic waste into ecobricks, with an Adiwiyata school-based approach. This training aims to increase students' environmental awareness, provide practical knowledge about plastic waste management, and encourage active participation in maintaining environmental cleanliness. The training methods include observing students' potential, demonstrating ecobrick making using presentation media, and project-based learning that actively involves students in the ecobrick-making process. The program also promotes the concept of 3R (reduce, reuse, recycle) as practical steps to reduce the negative impact of plastic on the environment. Evaluation results show that this training program successfully increased students' knowledge of plastic waste management and skills in making ecobricks. Additionally, active participation of students in Adiwiyata activities also increased, indicating higher environmental awareness among students